Efektivitas Ekstrak Daun Andong Terhadap Kesembuhan Luka Bakar Pada Kelinci (Oryctolagus cuniculus) - Prayitno, Suprapto; Edikamal, Sainal; Izza, Nurul (Media Farmasi, 2024)
The Andong plant (Cordyline fruticosa L.) is an ornamental plant that is often planted in people's yards in Indonesia. This plant is believed to be able to treat burns by using plant parts in the form of leaves which are processed by crushing them and then applying them to the wound area. In previous research, it was reported that andong leaves (Cordyline fruticosa L.) contain compounds, phenols, flavonoids, tannins and saponins. This plant plays a role in the process of closing wounds, due to its chemical content in the form of tannins which act as adstringents which can increase granulation in wounds and stop light bleeding. This research will test the effects of andong leaves as a medicine for burns using rabbit test animals. This research was carried out in the phytochemical and pharmacological toxicology laboratory at Pancasakti University, Makassar experimentally by testing the treatment of burn wounds on male rabbits using andong leaf extract (Cordyline fruticosa L.) containing flavonoids, saponins and tannins which have potential as a burn wound treatment. The diameter of the burn wound is indicated by the presence of burn wound healing activity. When giving andong leaf extract with a concentration of 5%, 10%, 15%. Giving the extract with a concentration of 15% had the best concentration with a healing percentage value of 95%, but at this concentration giving the positive control had a higher healing effect on burn wounds with a healing percentage value of 99.5%. So from the results of this research it can be concluded that andong leaf extract has effectiveness in healing burns in male rabbits and a 15% concentration of andong leaf extract has the highest effectiveness in healing burns, but this concentration does not exceed the effectiveness of healing when given the positive control given by bioplacenton.